Diagnostic Utility of ADC Value of the Spleen in Assessing Severity of Portal Hypertension in Cirrhosis of Liver - Himanshu Kumar Bhaiya; Smita Priyadarshini (International Journal of Health and Clinical Research, 2021)
Introduction: Chronic liver disease is a major spectrum of disease due to various aetiologies and portal hypertension (PH) is an essential manifestation of end-stage liver disease. However, accurate evaluation of PH severity and its management depends on invasive investigations like repeated upper gastrointestinal endoscopy and hepatic venous wedge pressure monitoring.Materials and methods: This prospective descriptive study was performed in our hospital from January 2020 to December 2020 on consecutive chronic liver disease patients referred to our Medicine Department. As this study is the first of its kind done on portal hypertension patients, we initially planned to find out any difference and the characteristics of the MRI (DWI) spleen findings of chronic liver disease/ cirrhosis patients compared to a control group with no liver disorders. For control, patients who undergo MRI abdomen investigation for other reasons with normal liver function test were included and were analysed. Results: We initially compared 15 patients from each group (Case and control) to analyse the difference in MRI findings of the spleen in DWI. We analysed the demographics of both groups and found to be matched with no significant difference between the age and sex of the patients (Median age 43 vs. 42, p= 0.9, sex 12 vs. 15 males, p= 0.6). When the clinical and biochemical parameters were compared between the two groups, there were obviously significant differences in parameters of chronic liver disease like hypersplenic features, liver span, spleen span and serum bilirubin, serum creatinine and INR. Conclusion: In conclusion, our results show that spleen ADC values vary among patients with liver cirrhosis and control subjects. Furthermore, ADC values in the spleen correlated well with the severity of portal hypertension and not significantly with the degree of liver disease. Thus, the spleen might only be of limited value for normalization of liver ADC values to determine cirrhosis. ADC measurements may allow for non-invasive evaluation of portal pressure and even in assessment of treatment response.